Pharmacokinetic herb-drug interaction study of selected traditional medicines used as complementary and alternative medicine (CAM) for HIV/AIDS - Awortwe, Charles (Stellenbosch : Stellenbosch University, 2015)
Thesis (DMed)--Stellenbosch University, 2015